ASSESSING KNOWLEDGE AND SELF-PERCEIVED COMPETENCY IN INTERNATIONAL HEALTH REGULATIONS (2005) AMONG FINAL-YEAR MPH STUDENTS IN NORTHERN NIGERIA:A CROSS-SECTIONAL STUDY (Journal of Pure and Applied Sciences (Science Forum), 2026)
Background:The International Health Regulations (2005) [IHR (2005)] provide a legally binding framework for preventing and responding to public health threats of international concern. However, limited empirical evidence exists regarding preparedness among future public health professionals in Nigeria.Methodology:This cross-sectional study assessed knowledge and self-perceived competency in IHR (2005) among final-year Master of Public Health (MPH) students in Northern Nigeria. A structured self-administered questionnaire was distributed to 201 respondents across selected universities. Data were analyzed using descriptive and inferential statistics.Results:Findings indicate a moderate level of IHR knowledge. Most respondents correctly identified the primary purpose of IHR (2005), the meaning of Public Health Emergencies of International Concern (PHEIC), and the role of the National IHR Focal Point. However, knowledge gaps were observed in technical areas such as core capacity requirements. Self-perceived competency across surveillance, risk communication, laboratory collaboration, emergency preparedness, and points-of-entry functions was generally moderate to high. Significant associations were found between university attended and knowledge level, as well as between previous IHR training and self-perceived competency.Conclusion:Although final-year MPH students demonstrate encouraging awareness and confidence, curriculum strengthening and structured practical training are necessary to enhance technical mastery and support Nigeria’s health security architecture.